DESIGN OF LABORATORY-SCALE ARCHIMEDES SCREW TURBINE PROTOTYPE - nahak, andre marce; Khwee, Kho Hie; Danial, Danial (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
The number of blades and helix range in the helical turbine are considered as internal parameters, while the outer radius of the turbine, turbine length, and turbine shaft inclination are regarded as external parameters. Both of these parameters define the geometric characteristics of the helical turbine. The geometric configuration of the Archimedes turbine can be determined using the formulation by Chris Rorres. The designed prototype of the Archimedes turbine has the following specifications: a total of 3 blades (N), an inner diameter (Di) of 11.4 cm, an outer diameter (Do) of 21.28 cm, a turbine length (L) of 80 cm, a screw pitch (Λ) of 25.53 cm, a number of turns (Z) of 3, and a turbine weight of 10.80 kg, with a turbine shaft inclination angle of 30°. From the research findings, the highest turbine performance was achieved at a water discharge of 0.006 m^3/s, resulting in a generated voltage of 41.02 V with a turbine rotation speed of 309.3 rpm.In this research, the experimental method was used, which involved testing the turbine performance by varying the water discharge under both unloaded and loaded conditions (load simulated using a lamp). Throughout the research process, each test data was recorded and analyzed using relevant formulas, and the results were presented in the form of graphs to facilitate drawing conclusions. From the research findings, the best turbine voltage regulation occurred at a water discharge of 0.0026 m^3/s, resulting in a voltage regulation of 22.38%.